Perbandingan Kinerja Keuangan Perbankan Syariah dan Perbankan Konvensional Periode 2016-2020 Menggunakan Metode RGEC (Studi pada Bank BRI dan BRI Syariah) - Muhammad Jefri; Sutopo; Abdullah Zawawi (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
Banks have a very important role in assisting human daily activities in carrying out economic activities. Banks cannot be separated from the life of modern society today because every economic activity is carried out through banks. There are generally 2 banks in Indonesia, namely Conventional Banks and Islamic Banks. Of the two banks, of course, have their own advantages and disadvantages. Therefore, it is necessary to make a comparison between their financial performance so that customers choose the best bank for them. . This study aims to examine and prove empirically about the comparison offinancial performance between PT. BRI Syariah Bank and PT. Bank BRI during the 2016-2019 The data used is secondary data in the form of financial reports from companies obtained from financial statements published by Bank Indonesia through the www.bi.go.id website, the OJK website and from the official websites of each bank. Data analysis was performed using financial ratio analysis consisting of CAR, NPL, ROA, ROE, BOPO, LDR. The analytical technique used to compare the financial performance of Bank Syariah Mandiri with Bank Muamalat Indonesia is the Independent sample t-test method. The results of the independent sample t-test statistical test showed that there was no significant difference between the CAR ratio of BRI Syariah Bank and BRI Bank. Meanwhile, the NPL, BOPO, ROA, ROE and LDR ratios of BRI Syariah Banks are significantly different from those of BRI Banks.